Effect of Yoga of Adaptive Yogasana Practice on the Flexibility and Psychomotor Variables in Intellectually Disabled Subjects. - Sriharisukesh, Naduvanthody; Pailoor, Subramanya; Sudharshanan, Sukanya; Chathambally, Riya (Indian Journal of Community Medicine)
Intellectual disability (ID) is a public health challenge affecting communities worldwide. ID is characterized by impaired physical and cognitive functioning and less engaged in physical activities. The objective of this study was to assess the impact of adaptive yoga practices on cognitive and motor abilities in the subjects with ID. Sixty-six subjects with mild and moderate IDs were purposively selected and randomly divided into experimental and control groups, with 33 subjects in each group. One month of adaptive yoga module was provided to the experimental group. To assess the impact of the yoga intervention, Functional Reach Test (FRT), Wall Toss Test (WTT), Finger Tapping Test (FTT), Sit-- Reach Test (SRT), and Six Letter Cancellation Test (SLCT) were administered. The experimental group showed a statistically significant improvement with P < 0.05 across all the parameters, whereas the control group could not observe a significant improvement. Based on the results, this study concludes that "one month of adaptive yoga module" delivered impact and helped to improve the dynamic balance, eye--hand coordination, neuro-motor function, spinal flexibility, and selective attention in ID-afflicted subjects.